Multiscale analysis of living benthic foraminiferal heterogeneity: Ecological advances from an intertidal mudflat (Loire estuary, France). (1st January 2022) - Thibault de Chanvalon, A.; Geslin, E.; Mojtahid, M.; Métais, I.; Méléder, V.; Metzger, E.
Abstract: An unprecedented sampling effort on the Loire estuary allowed a multi scale approach to identify parameters controlling density variations of benthic foraminifera. Indeed, the distances between the samples analysed for this study vary from 1 cm to hundreds of kilometres. To catch this range of distance variations, a model called Scale Variance Analysis was build describing the participation of each scale to the total observed variance. The SVA model requires, for each scale, the stability of relative variance. A comparison with the Moran's Index and experimental variogram is proposed showing coherent conclusions with the SVA analysis. The analysis shows that in order to maximize information on foraminiferal density variation, sampling campaigns should be designed with stations distant from few meters to 1 km, with a particular focus on the hectometre scale. A range of scale too rarely investigated in the community of benthic foraminifera ecology. Next, based on two intertidal mudflat stations separated of few hundred meters, the present study shows that for Ammonia tepida, the scale dependant preponderant parameters is the Chl a concentration in the top first centimetre. Contrastingly, the indicators of food quality such as the lability index and the oxygen penetration depth do not seem to affect A. tepida densities. This high quantity, low quality diet is interpreted as an opportunistic behaviour that is indirectly confirmed by a kinetic approach. This approach compares the deep infaunal microhabitat density with the shallow infaunal microhabitat density. The identical ratio indicates quick saturation of the available resources. Highlights: A new indicator to quantify spatial heterogeneity among different scale, the Scale Variance Analysis (SVA), is proposed. It revels higher heterogeneity of Ammonia tepida between 1 and 1000 m, in agreement with Moran's Index and experimental variogram. At the hectometer scale, direct correlation of A. tepida density with Chl a is observed. Equilibrium between deep and shallow infaunal population is rapidly reached for A . tepida probably due to rapid saturation of environmental capabilities.